Gender Differences in the Effect of Calcitriol on the Body Disposition and Excretion of Doxorubicin in Mice - Durna Corum, Duygu; Uney, Kamil (Springer Science and Business Media LLC, 2020)
The antitumor activity and toxicity of doxorubicin are potentiated and attenuated by calcitriol, respectively. Potentially, calcitriol can be combined with doxorubicin for clinical benefit in chemotherapy. To gain insight into the interaction between doxorubicin and calcitriol, proposed for combined use in cancer treatment, we studied calcitriol's effect on the plasma pharmacokinetics, tissue distribution and excretion of doxorubicin in female and male mice.The control and calcitriol-treated groups, including an equal number of both sexes, received corn oil and calcitriol (2.5 μg/kg), respectively, intraperitoneally every other day for 8 days. At day 9, doxorubicin was administered intraperitoneally at a 6 mg/kg dose to each group. Doxorubicin concentrations in biologic specimens were determined by a high-performance liquid chromatographic-ultraviolet detector and analyzed using a non-compartmental model.The plasma pharmacokinetics of doxorubicin were similar in the control and calcitriol-treated groups. While calcitriol did not alter the area under the plasma concentration-time curves (AUCs) and peak concentrations (Cmax) of doxorubicin in the small intestine and testis, it significantly reduced the AUCs and Cmax of doxorubicin in the lung, kidney, spleen, liver, stomach and ovaries. However, calcitriol increased the AUCs and Cmax of doxorubicin in the heart of females, brain of males and duodenum content and vitreous humor of female and male mice. The percent cumulative urine and fecal amounts of doxorubicin in calcitriol-treated mice were higher at 89.23% and 29.37% for female mice and 118.57% and 41.65% for male mice than those in the control mice, respectively.The tissue concentrations and excretion of doxorubicin in both female and male mice are influenced by calcitriol without changes in the plasma pharmacokinetics. The results from this study can provide insights to help obtain the optimal drug combination effects of doxorubicin with calcitriol in cancer treatment.
Keywords: Male; Antibiotics, Antineoplastic; Mice; Sex Factors; Calcitriol; Doxorubicin; Area Under Curve; Animals; Drug Interactions; Female; Tissue Distribution; Chromatography, High Pressure Liquid; 3. Good health